The African Peer Review Mechanism : towards Africa's governance audit - Molete, Nathan Teboho (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2008)
The concept of accountability has grown to become an integral part of a broader political and socio-economic transformation. Closely associated to it is the concept of "auditing" which has established itself as a main driving force of accountability and a core means of delivering it. The extent of the rise and expansion of "auditing" has subsequently come to influence every aspect of modern life and this has led to a situation in which practices have had to adapt to the principles of "auditing" processes. Auditing has become prevalent in both the public and private spheres and this impact has far reaching consequences. The concept of "auditing" is evident in the African Peer Review Mechanism (APRM) and is central to its review process. This thesis focuses on the concept of "auditing" in order to illustrate how the APRM has borrowed and applied insights from other disciplinary practices so as to enhance an understanding of accountability and transparency as features of "good governance" and to explicate how these concepts are conceived within the framework of the New Partnership for Africa's Development (NEPAD). It also clarifies the relationship that exists between "peer review" and "auditing" and argues that rather than being considered as two poles marked by distance from each other "auditing" and "peer review" are closely related and mutually constitutive.
Keywords: African Peer Review Mechanism; New Partnership for Africa's Development; Peer review -- Africa; Auditing -- Africa; Africa -- Politics and government -- 1960-